2014
DOI: 10.1128/jvi.02050-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Genotypes I and III in Japanese Encephalitis Virus Reveals Distinct Differences in Their Genetic and Host Diversity

Abstract: Japanese encephalitis (JE) is an arthropod-borne disease associated with the majority of viral encephalitis cases in the Asia-Pacific region. The causative agent, Japanese encephalitis virus (JEV), has been phylogenetically divided into five genotypes. Recent surveillance data indicate that genotype I (GI) is gradually replacing genotype III (GIII) as the dominant genotype. To investigate the mechanism behind the genotype shift and the potential consequences in terms of vaccine efficacy, human cases, and virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 67 publications
2
82
0
Order By: Relevance
“…Most of this saliva is actually released into the skin during probing, and components of the saliva substantially modify the immunological milieu at the probing site, often to the benefit of the virus [10]. Vertebrate host susceptibility depends upon numerous factors, including (i) the G Â G interaction between host and virus genotype [11,12], (ii) physiological condition, (iii) immune status, e.g. [13][14][15], and (iv) dose of virus delivered.…”
Section: The Double Life Of Arbovirusesmentioning
confidence: 99%
“…Most of this saliva is actually released into the skin during probing, and components of the saliva substantially modify the immunological milieu at the probing site, often to the benefit of the virus [10]. Vertebrate host susceptibility depends upon numerous factors, including (i) the G Â G interaction between host and virus genotype [11,12], (ii) physiological condition, (iii) immune status, e.g. [13][14][15], and (iv) dose of virus delivered.…”
Section: The Double Life Of Arbovirusesmentioning
confidence: 99%
“…Phyletic and adaptive evolutionary analyses predicted the positively selected sites within the GI and GIII alignment as potential genetic determinants affecting the genotype distribution. In addition, it has been suggested that increased viral multiplication in avians and mosquitoes as well as the more efficient replication and transmission cycle may be responsible for the genotype replacement (Han et al, 2014;Schuh et al, 2014). In this study, the recovered Japanese encephalitis viruses LAV-A222S and LAV-S327T with GI mutations showed a slight decrease in replication efficiency in C6/36 cells, and the possible role of host adaptations remains to be determined.…”
mentioning
confidence: 77%
“…In the first half of the 20th century, the majority of JEV isolates from humans belonged to GIII; however, over the last two decades, GI has gradually replaced GIII as the dominant circulating genotype in many areas of Asia, including China, Vietnam, Japan, India and Thailand (Ma et al, 2003;Nga et al, 2004;Nitatpattana et al, 2008;Pan et al, 2011;Parida et al, 2006;Sarkar et al, 2012). The mechanism underlying the genotype displacement as well as the impact of the genotype shift on transmission/outbreak control strategies remain largely unknown (Han et al, 2014;Schuh et al, 2013Schuh et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…20,40,41 Despite cross-neutralization studies with different genotype viruses strongly suggesting cross-protection in vivo, the reasons for the shift from G-III to G-I are unclear, although molecular analyses have suggested a role of restriction in host range and replication proficiency. 41 However, no detailed experimental analysis comparing various strains or serum samples have been performed, and the lack of reference reagents (genotype viruses as well as panel of antisera against each genotype virus) is an impediment for carrying out such comparative analyses (see below). It is important to note that serological cross-reactivity and/or cross-neutralization alone may not be sufficient, and a quantitative cut-off level may be needed to define serological subtypes among the various strains.…”
mentioning
confidence: 99%